Medical Students’ Perceptions of Online Learning During the COVID-19 Pandemic, Kuwait University: A National Survey - Alnaqi, Amar Ali; Buabbas, Ali Jasim; Jaafar, Nada Jalal; Alawadi, Aminah Mohammed; Alshawaf, Hamza Mohammed (Journal of medical and pharmaceutical sciences, 2024)
This study aimed to investigate the perceptions of Kuwait University (KU) medical students towards the online education during the COVID-19 pandemic—identifying the advantages and disadvantages of its use. An electronic questionnaire consisting of 28 questions was distributed from 15 February 2021 to 15 August 2021 to a nationally representative sample of all undergraduate medical students of KU via their university email addresses. A sample of 518 analytically valid responses was collected from 986 students (response rate = 52.5%). Most of the participating students (62.5%) considered their level of computer literacy to be intermediate. The number of hours spent on online learning increased dramatically during the COVID-19 crisis for all students from different phases. Avoiding traffic was the main perceived advantage of online learning (83.2%), while the main substantial drawback was having trouble connecting to the internet (72.58%). Most students (66.21%) believed that online learning had failed to replace the clinical teaching they had experienced before the pandemic. This study concluded that online learning was perceived with overall positive attitude among students suggesting it is a potentially valuable tool in delivering medical teaching. However, it failed to replace clinical and practical teaching, which are the core of medical training. It is recommended to improve the awareness level among tutors as well as the students, regarding the usefulness of online learning system, in addition to offer the required training and support to ensure the efficiency.